An implementation of IoT-based microwave sensing system for the evaluation of tissues moisture - Jilani, M.T. (Elsevier Ltd, 2018)
Internet-of-Things (IoT) is no longer just a buzzword. âThingsâ that are immensely connecting to the Internet, are now creating âSmartâ systems. However, heterogeneous devices and the dominance of propriety protocols are still the major challenges for practical application of such systems. This research work presents a practical application of a real-time microwave sensing system for the evaluation of tissues moisture. The work addresses two major challenges; first, the use of a highly sensitive microwave sensor to determine tissue moisture; second, to share the measurement with the remote users through an IoT-based system over the Bluetooth low-energy radio using open standards and protocols. The prototype shows significant changes in its resonance frequency, return loss and bandwidth (5.5â26) for the measured moisture content, which is also validated. This implementation demonstrates the feasibility of real-time monitoring of food quality. It also enables data-analytics that may help the industries to improve product quality, supply-chain and predicts demand in a more effective manner. Â© 2018